Prospective multicentre cohort study on 9154 surgical procedures to assess the risk of postoperative bleeding - a DESSI study - Koenen, Wolfgang; Weiß, Christel; Faulhaber, Jörg (Journal of the European Academy of Dermatology and Venereology, 2017)
Background To date, there is still a debate how to deal with patients receiving antithrombotic agents prior to surgical procedures on the skin. Objective To prospectively assess complications after dermatosurgical interventions, especially bleeding, depending on anticoagulation therapy. Methods Patients underwent surgery consecutively as scheduled, without randomization, whether or not they were currently taking anticoagulants. Nine institutions of the DESSI (DErmatoSurgical Study Initiative) working group documented patient data prospectively on a standardized study sheet prior to and after 9154 dermatosurgical interventions. Results Bleeding complications were observed in 7.14% of cases (654/9154 surgeries). A severe bleed requiring intervention by a physician occurred in 83 surgeries (0.91%). In multivariate analysis, INR, length of the defect, perioperative antibiotic treatment, current treatment with anticoagulation therapy, age and surgery on hidradenitis suppurativa/acne inversa (HS/AI) were significant parameters independently influencing the risk of bleeding. Discontinuation of phenprocoumon therapy and subsequent switching to low molecular weight heparin was associated with the highest risk of bleeding (9.26%). Conclusion Bleeding complications in skin surgery are generally rare. Even if slightly increased complication rates are found in patients taking anticoagulants during skin surgery, platelet inhibitors should not be stopped prior to surgery. If a surgical procedure in patients on a combination therapy of 2 or more antiplatelet cannot be postponed, it should be conducted with the patient remaining on combination therapy. Discontinuation of DOACs is recommended 24 h prior to surgery. Bridging of phenprocoumon should be terminated. In patients with a bleeding history, the INR value should be within the therapeutic range.